Development of a triplex crystal digital PCR for the detection of PRCoV, PRRSV, and SIV - Shi, Yuwen; Shi, Kaichuang; Ma, Yan; Yin, Yanwen; Long, Feng; Feng, Shuping; Mo, Meilan; He, Jiakang; Wei, Zuzhang (Frontiers in Veterinary Science, 2025)
Porcine respiratory coronavirus (PRCoV), porcine reproductive and respiratory syndrome virus (PRRSV), and swine influenza virus (SIV) are important pathogens of significant infectious diseases. They cause similar clinical respiratory symptoms, including fever, cough, runny nose, and respiratory distress, which makes these diseases difficult to distinguish from each other. In this study, three pairs of specific primers and TaqMan probes were designed for the conserved regions of the PRCoV S gene, PRRSV N gene, and SIV M gene, respectively. The annealing temperature, primer and probe concentrations, and reaction cycle were optimized, and a triplex crystal digital PCR (cdPCR) assay was established for the detection of PRCoV, PRRSV, and SIV. According to the test results, the assay was capable of specifically detecting PRCoV, PRRSV, and SIV, and there was no cross-reaction with other control swine viruses. Based on the Poisson distribution analysis, the limits of detection (LODs) for PRCoV, PRRSV, and SIV were 6.00, 5.75 and 6.00 copies/reaction, respectively, and the sensitivity was 26 times higher than those of the corresponding multiplex RT-qPCR. The coefficients of variation (CVs) of the intra-assay and inter-assay ranged from 0.19 to 1.84%. The assay was used to test 1,657 clinical samples, and the positivity rates of PRCoV, PRRSV, and SIV were 1.15, 12.79, and 2.05%, respectively. It showed diagnostic sensitivity and specificity of 100 and 99.82% for PRCoV, 100 and 99.24% for PRRSV, and 100 and 99.69% for SIV, respectively. These results indicated that the triplex cdPCR assay has strong specificity, high sensitivity, and excellent repeatability, which provides a valuable tool for the detection and differentiation of PRCoV, PRRSV, and SIV.